The superintendent's dilemma: Managing school district capacity as parents vote with their feet - Dennis N. Epple; Akshaya Jha; Holger Sieg (Quantitative Economics, 2018)
Many urban school districts in the United States and OECD countries confront the necessity of closing schools due to declining enrollments. To address this important policy question, we formulate a sequential game where a superintendent is tasked with closing down a certain percentage of student capacity; parents respond to these school closings by sorting into the remaining schools. We estimate parents' preferences for each school in their choice set using 4 years of student-level data from a mid-sized district with declining enrollments. We show that consideration of student sorting is vital to the assessment of any school closing policy. We next consider a superintendent tasked with closing excess school capacity, recognizing that students will sort into the remaining schools. Some students will inevitably respond to school closings by exiting the public school system; it is especially difficult to retain higher achieving students when closing public schools. We find that superintendents confront a difficult dilemma: pursuing an equity objective, such as limiting demographic stratification across schools, results in the exit of many more students than are lost by an objective explicitly based on student retention.
Keywords: C35; C52; C60; I20; 330; School closing; school choice; demand for public schools; peer effects